Vision Screening in Infants Attending Immunization Clinics in a Developing Country. (February 2020) - Jac-Okereke, Chinwe Cynthia; Jac-Okereke, Chukwunonso Azubuike; Ezegwui, Ifeoma Regina; Okoye, Obiekwe
Background: Vision screening in infants is an important part of the medical care of children as some eye abnormalities, if not treated in the first few months or years of life, can lead to irreversible vision loss.Objective: The objective of this cross-sectional, descriptive study was to identify ocular anomalies among infants attending immunization clinics in Nigeria and refer promptly and appropriately.Methodology: Infants were screened across 6 immunization clinics. Screening activities included relevant ocular history, vision assessment, external ocular examination, ocular motility, Hirschberg's test, pupil examination, and the red reflex test. Infants with abnormal findings were referred for comprehensive eye examination.Result: Of the 142 infants who underwent vision screening, 29 were referred. These referrals were either as a result of ocular abnormalities (n = 22) or presence of risk factors from history (n = 7). The prevalence of ocular abnormalities was 15.5% and neonatal conjunctivitis (38%), was the commonest ocular abnormality found. Others were bacterial conjunctivitis (14%), nasolacrimal duct obstruction (14%), strabismus (14%), capillary hemangiomas (10%), iris nevi (5%), and vernal keratoconjunctivitis (5%). Of the 7 infants referred based on history alone, 6 (85.7%) had a history of prematurity.Conclusion: Conjunctivitis, strabismus, congenital nasolacrimal duct obstruction, and capillary hemangioma are some of the prevalent disorders seen in infants at immunization clinics in Nigeria. Babies at risk of retinopathy of prematurity (preterm birth and oxygen therapy) can be identified. Immunization clinics can serve as good points of vision screening for infants in developing countries to facilitate prompt referral and treatment.